Peering into the heart of the M82 starburst. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Fenech, Danielle; Muxlow, Tom; Beswick, Rob; Argo, Megan
Abstract: We present multi-epoch millarcsecond resolution images of the most compact supernova remnants in the nearby starburst galaxy M82, spanning 25 years of evolution. In particular, we will briefly discuss the new transient source first detected in 2009 as well as the unusual object 41.95+57.5 and its potential as a GRB afterglow.